2016
DOI: 10.1016/j.cmet.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila TNF Eiger Is an Adipokine that Acts on Insulin-Producing Cells to Mediate Nutrient Response

Abstract: Adaptation of organisms to ever-changing nutritional environments relies on sensor tissues and systemic signals. Identification of these signals would help understand the physiological crosstalk between organs contributing to growth and metabolic homeostasis. Here we show that Eiger, the Drosophila TNF-α, is a metabolic hormone that mediates nutrient response by remotely acting on insulin-producing cells (IPCs). In the condition of nutrient shortage, a metalloprotease of the TNF-α converting enzyme (TACE) fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 57 publications
6
194
2
Order By: Relevance
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/253542 doi: bioRxiv preprint first posted online Jan. 24, 2018; Our findings that IMD specifically affects insulin activity collaborate reports that the Drosophila TNFα homolog, Eiger, regulates production of insulin peptides in the brain (Agrawal et al, 2016), and that the FOXO homolog, Forkhead, regulates intestinal metabolism, and survival after infection in adult Drosophila (Bolukbasi et al, 2017). In addition, several studies identified interaction points between immune and insulin responses in the fly.…”
Section: Discussionsupporting
confidence: 62%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/253542 doi: bioRxiv preprint first posted online Jan. 24, 2018; Our findings that IMD specifically affects insulin activity collaborate reports that the Drosophila TNFα homolog, Eiger, regulates production of insulin peptides in the brain (Agrawal et al, 2016), and that the FOXO homolog, Forkhead, regulates intestinal metabolism, and survival after infection in adult Drosophila (Bolukbasi et al, 2017). In addition, several studies identified interaction points between immune and insulin responses in the fly.…”
Section: Discussionsupporting
confidence: 62%
“…In larvae, low protein diet induces Egr secretion from FBs into the hemolymph through inhibition of TOR (target of rapamycin) and induction of TNFα-converting enzyme (TACE), which cleaves Egr from the membrane (1). Egr binds to IPCs through the Grindelwald (Grnd) receptor, which acts through the Jun N-terminal kinase (JNK) pathway to inhibit Dilp2/5 mRNA expression and larval growth (1). In addition, under high sugar diet, Grnd signaling in FBs induces insulin resistance.…”
Section: Drosophila As a Model System To Dissect Interorgan Communicamentioning
confidence: 99%
“…Second, other signals from the brain and fat body are also associated with this biological process. For example, Agrawal et al argued that TNF-α converting enzyme (TACE)-mediated Eiger (Egr) secretion from the fat body contributes to organismal growth through Grindelwald (Grnd) activity in the brain in response to a normal protein diet (Agrawal et al, 2016). …”
Section: Links Between Larval Organsmentioning
confidence: 99%